Pengaruh Media Sosial dan Literasi Ekonomi Terhadap Impulsive Buying Siswa - Nailatus Shofia; Mohamad Arief Rafsanjani (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Impulse buying is a form of consumer behavior characterized by a sudden and strong emotional urge to purchase a product without any planning or logical consideration. People who make impulsive purchases tend to ignore the need, price, and long-term benefits of the product they purchase. This phenomenon is common among teenagers and students, who are psychologically still in the process of searching for their identity and are easily influenced by their social environment and the information they receive, especially through social media. Social media plays a crucial role in shaping modern consumer behavior. Platforms such as Instagram, TikTok, and Facebook offer engaging visual content, intensive product promotions, and influencer marketing campaigns that can create an emotional urge to purchase. The speed of information access, interactivity, and personalized recommendations make social media one of the most effective and influential marketing channels, especially among the younger generation. On the other hand, a lack of economic literacy makes students more vulnerable to the temptation of impulsive buying due to their limited ability to manage personal finances and low awareness of the importance of financial planning. This study aims to examine the influence of social media and economic literacy on impulsive buying behavior in students. The method used was quantitative, with 187 respondents selected through a simple random sampling technique based on the Slovin formula. Data were collected using an online questionnaire via Google Form and analyzed using multiple linear regression using SPSS version 25. The results showed that social media had a positive and significant effect on students' impulsive buying behavior, while economic literacy had a negative and significant effect. Simultaneously, these two variables also had a significant effect on impulsive buying behavior.